Long‐Term Response of Neuropathic Pain to Intravenous Immunoglobulin in Relapsing Diabetic Lumbosacral Radiculoplexus Neuropathy. A Case Report. Issue 2 (24th October 2013) - Tamburin, Stefano; Magrinelli, Francesca; Favaro, Flaviano; Briani, Chiara; Zanette, Giampietro
Abstract Diabetic lumbosacral radiculoplexus neuropathy (DLRPN) is a rare painful peripheral neuropathic complication of diabetes mellitus. The clinical features of DLRPN include severe neuropathic pain, weakness, atrophy, and sensory loss in the lower limbs with asymmetrical distribution. Nerve ischemia due to inflammation and microvasculitis has been suggested as the pathophysiological mechanism for DLRPN. Analgesics and drugs for neuropathic pain often cannot achieve adequate pain control in DLRPN. Some reports suggest that intravenous immunoglobulin (IVIg) may reduce pain in DLRPN, but the mechanisms of this effect are unclear. We report a patient with relapsing DLRPN who was followed up for 8 years and whose pain improved after IVIg on nine occasions. We measured serum cytokines before and after IVIg; serum tumor necrosis factor α was increased when the patient reported pain and normalized after IVIg in parallel with pain improvement. Our data extend the notion that some types of pain, including peripheral neuropathic pain, may respond to IVIg and give some clue on the mechanism of this therapeutic effect. They are also consistent with the suggested role of the immune system in the pathophysiology of neuropathic pain and offer support to the hypothesis that cytokines may contribute to the pathogenesis of neuropathic pain.